2002
DOI: 10.1073/pnas.152126799
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of somatic hypermutation specificity and A-T base pair substitution errors by DNA polymerase η during copying of a mouse immunoglobulin κ light chain transgene

Abstract: To test the hypothesis that inaccurate DNA synthesis by mammalian DNA polymerase (pol ) contributes to somatic hypermutation (SHM) of Ig genes, we measured the error specificity of mouse pol during synthesis of each strand of a mouse Ig light chain transgene. We then compared the results to the base substitution specificity of SHM of this same gene in the mouse. The in vitro and in vivo base substitution spectra shared a number of common features. A highly significant correlation was observed for overall subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 48 publications
(85 reference statements)
6
110
0
Order By: Relevance
“…The base-substitution spectrum of SHM from XP-V patients is altered with severely decreased mutations at A:T pairs (11,17,18). Similar suppression of A:T to G:C mutations was observed in the POLH-deficient mice (19)(20)(21). Interestingly, the MSH2-MSH6 heterodimer interacts and stimulates Pol η activity in vitro (22), and mutations of A:T base pairs were abolished in SHM when both POLH and MSH2 genes were knocked out (23).…”
Section: π-Cation Stacking | A-to-g Transition | Immunoglobulinmentioning
confidence: 81%
“…The base-substitution spectrum of SHM from XP-V patients is altered with severely decreased mutations at A:T pairs (11,17,18). Similar suppression of A:T to G:C mutations was observed in the POLH-deficient mice (19)(20)(21). Interestingly, the MSH2-MSH6 heterodimer interacts and stimulates Pol η activity in vitro (22), and mutations of A:T base pairs were abolished in SHM when both POLH and MSH2 genes were knocked out (23).…”
Section: π-Cation Stacking | A-to-g Transition | Immunoglobulinmentioning
confidence: 81%
“…Whereas such a strand-specific repair would be compatible with the equalization of mutations between G and C bases, and the A over T bias observed in V gene mutations (Fig.4), the proposition deserves additional studies, as the mutations reported do not fit with the pattern expected from Polη-mediated repair 60 .…”
Section: A Model For Shm: Two Competitive Rather Than Alternative Patmentioning
confidence: 88%
“…Polη is not a processive enzyme and therefore favours the synthesis of a few nucleotides (short-patch DNA synthesis). Mutagenicity of Polη was estimated using a Vκ template sequence when synthesizing either the transcribed or the non-transcribed strand in vitro 60 . Interestingly, despite the fact that this assay monitored the error rate of the polymerase during the synthesis of a few hundred bases that may not occur in vivo, a strong correlation with the in vivo pattern of mutations at A/T base pairs was observed, in particular during synthesis of the coding strand (the non-transcribed strand), although hotspots on both coding and non-coding strands were clearly observed.…”
Section: Polη the Study Of Patients Affected By The Xeroderma Pigmenmentioning
confidence: 99%
“…Notably, we detected the opposite effect when we expressed Poll in a hypermutating cell line, with larger numbers of heavily mutated clones compared to control cells [15]. Polg deletion results in fewer mutations as well as targeting alteration [40], whereas Poll does not appear to affect targeting, nonetheless argues against this hypothesis.…”
Section: Discussionmentioning
confidence: 71%